Experimentos with plants said to be toxic in cattle in the State of Rio de Janeiro, which resultad negative or caused slight shortlastting symptoms - Tokarnia, Carlos Hubinger; Canella, Camillo F. C.; Döbereiner, Jürgen (Pesquisa Agropecuaria Brasileira, 2014)
Thirteen plants indigenous to the State of Rio de Janeiro, Brazil, which had either been reported in the literature or were held in common belief to be poisonous, were studied. The plant materials were orally fed to cattle and observations made. The following plant species and part of the plant fed were used: Acnistus cauliflores (leaves and buds), Crataeva tapia (leavea and buds), Datura arborea (leaves, buds and flowers), Davilla rugosa (leavea), Eclipta alba (aerial parts), Guarea trichilioides (leaves), Oxypetalum Banksii (aerial parts), Oxypetalum umbellatum (aerial parts), Rhynchosia pyramidalis (aerial parts without the woody stalk), Ricinus comnunis (bunches with still green seeds), Solanum nigrum (aerial parts with flowers and fruits, most of them green), Tabenaemontana laeta (leaves and buds), Tagetes minuta (upper flowering parts). The experimental animals suffered no obvious adverse effects to any of the plant material given, with exception of two plants, which caused in part of the animals slight shortlasting symptoms. These plants were Datura arborea (leaves, buds and flowers) and Ricinus communis (bunches with still green seeds).